Strategic Management and Development Trend of Sino-foreign Cooperative University in the New Era of Open Education Development - Chen Zeng (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
With China's higher education entering a new era of open development, the state clearly proposes to "carry out high-level cooperation in running schools with world-class resources, and further expand the opening up of education." Therefore, further strengthening the construction of Sino-foreign cooperative university coincides with the national development strategy. Sino-foreign cooperative university must seize this important historical opportunity, strengthen strategic management, and contribute to high-quality leapfrog development. In the face of the new era of open education development, Sino-foreign cooperative university should make full use of the high-quality education resources and institutional advantages introduced, and combine with the current development situation, make clear its own strategic positioning and focus, and take reasonable strategic measures.